Technical communication or information design? : a New Zealand perspective : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Business Studies - Reynolds, Alison (Massey University, 2002)
This research aims to investigate and analyse current trends in New Zealand technical communication. Specifically, it considers how these trends compare to those evident in the United States of America, where the research shows a contemporary paradigm shift occurring from technical communication to information design. The findings of this research show that New Zealand technical communicators do have the core competencies of information designers and that technical communication in New Zealand is, indeed, undergoing a similar change to that happening internationally, especially in the United States of America. The research methodology of this study uses data from two sources: • Current literature on trends in technical communication and information design • A qualitative survey of New Zealand technical communication practitioners. Current literature in the field describes trends that suggest a shift in the core competencies of contemporary technical communicators. This literature largely emerges from an American context. These trends include: • A need for technical communicators to be part of the iterative design process of products and to be user advocates • A change from paper-based documents to online information • The advent of the Internet • The advent of single sourcing and knowledge management computer tools. This study concludes that technical communicators need a broad range of competencies to adapt to the trends described, and that it is no longer adequate for a professional technical communicator to simply be a good writer and document designer. However, this study also shows that New Zealand practitioners currently do demonstrate the key competencies of information designers, including highly developed skills in problem solving, planning and managing the process of product development, information management, usability testing, while continuing to carry out the more obvious tasks of technical communication, such as writing, audience analysis and document design. The main difference between the American and New Zealand technical communication trends analysed here is that technical communication in New Zealand is just becoming recognised as a profession, whereas in the States it has existed since World War Two (WW2). Because of this historical difference, it seems that New Zealand practitioners are not bound by traditional job titles as their American counterparts are, and also tend to have position designations that are more readily recognised by clients and users, such as "documentation specialist", or "document developer". To date, no formal research on technical communication or information design has been completed in New Zealand. Further research is recommended then, in order to gain a more detailed profile of practitioners and practices. This research could be used to address areas such as training needs and, more widely, could continue to raise awareness of the profession in New Zealand. Further research should focus on gathering information on the geographical distribution of practitioners, profiling tasks, tools and jobs, analysing salaries, and examining potential academic programme profiles that could meet the needs of potential information designers.
Keywords: Communication of technical information; Technical writing